2020
DOI: 10.1088/1757-899x/829/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Tests of Joints of Glued Wooden Structures

Abstract: The use of large-span structures made of glued wood in countries with large timber reserves in Finland, Sweden, Norway, Russia, the USA and Canada has shown that this can be quite interesting and expressive from the architectural position of the building. Sports facilities, sports and sports facilities, sports facilities, sports and cultural facilities. The practice of building bridges made of glued wood in these countries shows that they have been in operation for decades without additional operating costs. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…At least two main reasons may be responsible for the absence of an obvious relation of genetic diversity and pedunculate oak population sizes. The reduction in the area of populations became significant only in the last millennium due to the increasing economic development of the territory (Kozharinov and Borisov 2012;Aruova et al 2020). A study of historical data showed that relatively abundant broad-leaved forests existed in the east section of the Russian Plain even until the end of the eighteenth century (Gorchakovsky 1968).…”
Section: Discussionmentioning
confidence: 99%
“…At least two main reasons may be responsible for the absence of an obvious relation of genetic diversity and pedunculate oak population sizes. The reduction in the area of populations became significant only in the last millennium due to the increasing economic development of the territory (Kozharinov and Borisov 2012;Aruova et al 2020). A study of historical data showed that relatively abundant broad-leaved forests existed in the east section of the Russian Plain even until the end of the eighteenth century (Gorchakovsky 1968).…”
Section: Discussionmentioning
confidence: 99%
“…27 Thus, the obtained data on compaction and recommendations on forest transportation can be applied in simulating the design of an innovative skidder, which allows for increasing the productivity of the skidding system. 28,29 However, the question of whether these wood covers provide sufficient protection in all situations is disputable. Another argument to consider is the displacement of nutrients in forest plantations, since all organic matter usually spread throughout the plantation is now concentrated on the skidding trails.…”
Section: Resultsmentioning
confidence: 99%
“…27 Thus, the obtained data on compaction and recommendations on forest transportation can be applied in simulating the design of an innovative skidder, which allows for increasing the productivity of the skidding system. 28,29…”
Section: Resultsmentioning
confidence: 99%
“…Joints of wooden frame elements can be addressed in several ways. One can use glued joints [ 30 , 31 , 32 ], for example, by means of glued steel bars. Another possibility is to form a frame connection from a post, which is arranged in a V-shape [ 33 ].…”
Section: Introductionmentioning
confidence: 99%